Spatial and Socio-Economic Determinants of Advanced Level Stream Selection in the Norwood Division, Nuwara Eliya, Sri Lanka - Kirubananthan, N.; Thanushan, R. (Faculty of Arts, University of Jaffna, Sri Lanka, 2025)
This study investigates the holistic interplay of multiple factors influencing advanced-level stream selection in the Norwood Divisional Secretariat of Nuwara Eliya, Sri Lanka. The research highlights a significant disparity, with a high number of students opting for Arts and Commerce subjects, while fewer students choose Mathematics, Science and Technology subjects. The primary objective of this study is to identify the sub-factors affecting stream selection, examine their interdependence and propose strategies to provide evidence-based recommendations to educational stakeholders. The study focused on 25 Tamil medium Advanced Level schools in the area, selected using a simple random sampling method. Primary data was collected from students and teachers through questionnaires, interviews and direct observation. Secondary data was gathered from the Hatton Educational Department. Additionally, ArcGIS software, SPSS and Microsoft Excel were used to map student residences, school locations and private educational institutions, while simple statistical analysis was performed. SWOT and TOWS Matrix analyses were also conducted. Key findings reveal that traveling distance and transportation are crucial factors influencing stream selection, with 29% of students living more than 20 km away from their schools and 95% walking to schools. These factors, combined with the cost of transportation, significantly impact students’ stream choices. Additionally, 76% of students did not choose their A/L education stream voluntarily and 85% expressed a desire to pursue a different stream. The study concludes that there is a pressing need to improve the Mathematics and Science stream selection in the Norwood area to create more career opportunities for students, while also enhancing the Arts stream. This research confirms that multiple factors are interrelated in the selection of academic courses for higher education.
Keywords: Norwood divisional secretariat; G.C.E. advanced level stream selection; Spatial determinants; Socio-economic determinants; Interplay